Lymphatic vasculature in the central nervous system - González-Hernández, Sara; Mukouyama, Yoh-suke (Frontiers in Cell and Developmental Biology, 2023)
The central nervous system (CNS) is considered as an immune privilege organ, based on experiments in the mid 20th century showing that the brain fails to mount an efficient immune response against an allogeneic graft. This suggests that in addition to the presence of the blood-brain barrier (BBB), the apparent absence of classical lymphatic vasculature in the CNS parenchyma limits the capacity for an immune response. Although this view is partially overturned by the recent discovery of the lymphatic-like hybrid vessels in the Schlemm’s canal in the eye and the lymphatic vasculature in the outmost layer of the meninges, the existence of lymphatic vessels in the CNS parenchyma has not been reported. Two potential mechanisms by which lymphatic vasculature may arise in the organs are: 1) sprouting and invasion of lymphatic vessels from the surrounding tissues into the parenchyma and 2) differentiation of blood endothelial cells into lymphatic endothelial cells in the parenchyma. Considering these mechanisms, we here discuss what causes the dearth of lymphatic vessels specifically in the CNS parenchyma.